2020
DOI: 10.3390/brainsci11010024
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Splicing in GJB1 and the Relevance of 5′ UTR in CMTX1 Pathogenesis

Abstract: The second most common form of Charcot-Marie-Tooth disease (CMT) follows an X-linked dominant inheritance pattern (CMTX1), referring to mutations in the gap junction protein beta 1 gene (GJB1) that affect connexin 32 protein (Cx32) and its ability to form gap junctions in the myelin sheath of peripheral nerves. Despite the advances of next-generation sequencing (NGS), attention has only recently also focused on noncoding regions. We describe two unrelated families with a c.-17+1G>T transversion in the 5′ un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This results in a decrease in the mRNA and, consequently, protein expression level. This mechanism was detected for 5′‐UTR splice‐site variants of various genes 12–14 . Recently, it was shown that splice‐site variant in the POMC 5′‐UTR (c.‐71 + 1G > A) leads to a decrease in both mRNA and protein expression level.…”
Section: Discussionmentioning
confidence: 93%
“…This results in a decrease in the mRNA and, consequently, protein expression level. This mechanism was detected for 5′‐UTR splice‐site variants of various genes 12–14 . Recently, it was shown that splice‐site variant in the POMC 5′‐UTR (c.‐71 + 1G > A) leads to a decrease in both mRNA and protein expression level.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, Benedetti et al proved that a c.‐16‐3C>G substitution activated a cryptic splice site which resulted in the deletion of the first 278 nucleotides of exon 2, which consisted of part of our result (Benedetti et al, 2010). However, it was previously reported that the change of the canonical splice site sequence (c.‐17+1G>T) causes the retention of the whole intron 1 into the mRNA and demonstrated a 70% reduction of the transcript level of GJB1 expression (Boso et al, 2020). When compared to this report, our patients also had fairly typical clinical, neurophysiological and pathological features, bearing a phenotype that co‐segregated with the variant.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter P2 positions in intron 1 of transcript NM_001097642 and is responsible for the expression of the transcript NM_000166.6 in the peripheral nervous system. Though these two different transcripts include different 5′UTR, they provide mRNAs with identical coding regions (Boso et al, 2020). To date, most of the known variants are in the coding region, with the majority being missense mutations and rarer cases with frameshift and premature stop codon mutations or ample deletions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most mutations are missense variants and are believed to cause predominantly loss of function phenotypes [249]. Interestingly, several variants in the non-coding regions of GJB1 have been demonstrated to cause CMT1X [250][251][252], at least in some cases due to abnormal splicing of GJB1 [253]. Furthermore, copy number variations in GJB1 have also been identified in patients with CMT1X [254,255].…”
Section: Connexin 32-associated Neuropathy: Epidemiology and Clinical...mentioning
confidence: 99%